Factors Influencing Renewable Energy Technological Innovation in Malaysia - Raza, Muhammad; Alshebami, Ali Saleh; Sibghatullah, Amena (International Journal of Energy Economics and Policy, 2020)
The objective of the research paper is to investigate the factors that influence innovation in renewable energy technology in Malaysia. The study has been designed to assess this newer means of generating energy through the means of wind, water and other resources. The researcher has aimed to evaluate these factors and find its influence on the Renewable Energy Technological Innovation. This study has analyzed the influence of the independent variable of the study over the dependent variable with the help of statistical analysis tool, which is Stata. Furthermore, using the Stata, researcher has applied two tests mainly in this study such as descriptive analysis along with that ADF. Moreover, based upon the factors of the study, ARDL model has been applied in to execute the study in an efficient manner. In case of renewable energy consumption, one of the most important aspect necessary to mention is that the domestic and commercial users who are not producing renewable energy at their own does not experience any difference while using the renewable energy as compared with the energy produced by conventional methods. Keywords: Renewable Energy, Technological Innovation, Energy Consumption, Wind, Solar JEL Classifications: O32, K32 DOI: https://doi.org/10.32479/ijeep.10455